2022
DOI: 10.1128/aem.02270-21
|View full text |Cite
|
Sign up to set email alerts
|

Second Messenger c-di-GMP Modulates Exopolysaccharide Pea-Dependent Phenotypes via Regulation of eppA Expression in Pseudomonas putida

Abstract: Exopolysaccharides (EPSs) Pea is essential for wrinkly colony morphology, pellicle formation, and robust biofilm production in Pseudomonas putida . The second messenger cyclic diguanylate monophosphate (c-di-GMP) induces wrinkly colony morphology in P. putida through unknown mechanism(s). Herein, we found that c-di-GMP modulated wrinkly colony morphology via regulating expression of eppA ( PP_5586 ), a small individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…We identified 4 c-di-GMP metabolic genes, including VA4033 , VA1591 , VA0356 , and VA0088 , all with intact active sites for the GGDEF domain ( Table 1 ), involved in the enhanced rugose colony phenotypes on LB agar plates ( Figure 2 ). It is well known that there is a strong correlation between the phenotypes of colony rugosity, biofilm formation and EPS production, and moreover, these phenotypes are often accompanied by elevated intracellular c-di-GMP levels ( Nakhamchik et al, 2008 ; Romling et al, 2013 ; Wu et al, 2020 ; Xiao et al, 2022 ). In general, enhanced EPS production often results in rugose colony phenotypes ( Casper-Lindley and Yildiz, 2004 ; Beyhan et al, 2008 ), a phenomenon also demonstrated in the present work, for example, overexpression strains ∆ VA1591 p1591, ∆ VA4033 p4033, ∆ VA0356 p0356, and ∆ VA0088 p0088 produced rugose colonies that also had strong CR binding capacities ( Figures 2 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…We identified 4 c-di-GMP metabolic genes, including VA4033 , VA1591 , VA0356 , and VA0088 , all with intact active sites for the GGDEF domain ( Table 1 ), involved in the enhanced rugose colony phenotypes on LB agar plates ( Figure 2 ). It is well known that there is a strong correlation between the phenotypes of colony rugosity, biofilm formation and EPS production, and moreover, these phenotypes are often accompanied by elevated intracellular c-di-GMP levels ( Nakhamchik et al, 2008 ; Romling et al, 2013 ; Wu et al, 2020 ; Xiao et al, 2022 ). In general, enhanced EPS production often results in rugose colony phenotypes ( Casper-Lindley and Yildiz, 2004 ; Beyhan et al, 2008 ), a phenomenon also demonstrated in the present work, for example, overexpression strains ∆ VA1591 p1591, ∆ VA4033 p4033, ∆ VA0356 p0356, and ∆ VA0088 p0088 produced rugose colonies that also had strong CR binding capacities ( Figures 2 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The designation ‘cfc’ comes from a ‘crinkle‐free colony’, which is the characteristic phenotype of the P. putida reference strain KT2440. The nearly species‐specific Pea EPS is specifically required for the acquisition of the crinkle phenotype induced by increased c‐di‐GMP (Matilla et al, 2011; Xiao et al, 2022).…”
Section: Building and Demolishing: C‐di‐gmp Dgcs And Pdesmentioning
confidence: 99%